Platelet-to-Lymphocyte Ratio and Neutrophil-to-Lymphocyte Ratio in Patients With Newly Diagnosed Moyamoya Disease: A Cross-Sectional Study - Ma, Wenyuan; Cui, Changmeng; Feng, Song; Li, Genhua; Han, Guangkui; Liu, Jilan; Qin, Xianyun; Hu, Yawei; Wang, Mengjie; Zhang, Lu; Jin, Feng (Frontiers in Neurology, 2021)
Inflammation has been shown to play a pivotal role in the pathogenesis of moyamoya disease (MMD). Platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) are inexpensive and reliable biomarkers of inflammation. Nevertheless, evidence regarding the relationship between PLR and NLR in patients with MMD is limited. The aim of this study was to investigate the relationship between PLR and NLR in Chinese patients with newly diagnosed MMD. Patients and methods: A cross-sectional study was performed including 261 patients with newly diagnosed MMD who were enrolled from Department of Neurosurgery, Affiliated Hospital of Jining Medical University, Jining, Shandong, China, from 24 March 2013 to 24 December 2018. The clinical characteristics were evaluated for each patient. Univariate analysis, smooth curve fitting and multivariate piecewise linear regression were performed. Results: The mean levels or median values (interquartile range) of PLR and NLR were 146.979 ± 51.203 and 2.241 (1.589-2.984), respectively. The univariate analysis results showed a significant positive correlation between PLR and NLR levels (P<0.001). Furthermore, a nonlinear relationship was observed between PLR and NLR by smooth curve fitting after adjusting for possible confounders. A multivariate piecewise linear regression model revealed a significant positive correlation between PLR and NLR when the PLR level was lower than 219.82 (β 0.012, 95% CI 0.005, 0.019; P=0.001). PLR was also significantly positively associated with NLR when PLR concentrations were greater than 219.82 (β 0.098, 95% CI 0.069, 0.128; P＜0.001). Conclusion: In patients with MMD, there seemed to be a positive association between PLR and NLR. This may help to further explain the role of inflammation in the occurrence and development of MMD.